Marked reduction of cerebellar deficits in upper limbs following transcranial cerebello-cerebral DC stimulation: tremor reduction and re-programming of the timing of antagonist commands - Grimaldi, Giuliana; Oulad Ben Taib, Nordeyn; Manto, Mario U.; Bodranghien, Florian (Frontiers in Systems Neuroscience, 2014)
Cerebellar ataxias represent a very heterogeneous group of disabling disorders for which we lack effective symptomatic therapies in most cases. There is currently an intense interest in the use of non invasive transcranial DC stimulation (tDCS) to modulate the activity of the cerebellum in ataxic disorders. We performed a detailed laboratory assessment of the effects of transcranial cerebello-cerebral DC stimulation (tCCDCS, including a sham procedure) on upper limb tremor and dysmetria in 2 patients presenting a dominant spinocerebellar ataxia (SCA) type 2, one of the most common SCAs encountered during practice. Both patients had a very similar triplet expansion size in the ATXN2 gene (respectively 39 and 40 triplets). tCCDCS reduced both postural tremor and action tremor, as confirmed by spectral analysis. Quadratical PSD (power spectral density) of postural tremor dropped to 38.63 % and 41.42 % of baseline values in patient 1 and 2, respectively. The integral of the subband 4-20 Hz dropped to 46.9 % and 62.3 % of baseline values, respectively. Remarkably, tCCDCS cancelled hypermetria and reduced dramatically the onset latency of the antagonist EMG activity associated with fast goal-directed movements towards 3 aimed targets (0.2, 0.3 and 0.4 rad). Following tCCDCS, the latency dropped from 108-98 msec to 63-57 msec in patient 1, and from 74-87 msec to 41-46 msec in patient 2 (mean control values +/- SD: 36 +/- 8 to 45 +/- 11 msec), corresponding to a major drop of z scores for the 2 patients from 7.12 +/- 0.69 to 1.28 +/- 1.27 (sham procedure: 6.79 +/- 0.71). This is the first demonstration that tCCDCS improves upper limb tremor and hypermetria in SCA type 2. In particular, this is the first report of a favourable effect on the onset latency of the antagonist EMG activity, a neurophysiological marker of the defect in programming of timing of motor commands. Our results indicate that tCCDCS should be considered in the symptomatic management of upper limb motor de